The Development of Student Worksheets Based on Jember Local Wisdom for Reading and Viewing Narrative Text Skills in Grade IV Students - Nabilah, Fikriyyah Tasyah; Suhartiningsih, Suhartiningsih; Wardoyo, Arik Aguk (Jurnal Basicedu, 2025)
The current implementation of the Independent Curriculum has made many changes in education in Indonesia, but there are many challenges faced in improving the quality of learning, especially by teachers to develop teaching materials. This development research aims to assist teachers in maximizing learning vocabulary interpretation materials through LKPD based on local wisdom for reading skills and viewing narrative texts that are valid and effective to use. The method used in this development research is a model (Research and Development) by Borg and Gall. Data collection was carried out through interviews, product validation, response questionnaires, and learning outcome test sheets. The LKPD developed can be declared valid based on the score of the media, language, and material expert validators, which reaches a score of 82.11, which is a very valid category. The effectiveness of the LKPD shows results that can be declared effective. The increase achieved by students from pre-test to post-test, namely from 27.27% increased to reach 59.09% completeness.